Pola Komunikasi Dakwah Pada Konten Animasi YouTube Rizky Riplay - Rachma Putri; Bambang Saiful Ma'arif; Nia Kurniati Syam (UNISBA Press, 2025)
Abstract. This study aims to know the Islamic message conveyed in Rizky Riplay's YouTube animation content, Rizky Riplay's role as a communicator in delivering da'wah through animated media on YouTube. The response of subscribers to the content of Rizky Riplay's YouTube animation account, and the pattern of da'wah communication in the animated content of Rizky Riplay's YouTube account. This research uses descriptive qualitative. Data were collected through interviews, observation, and content analysis. By using Lievrouw & Livingstone's New Media theory. The results showed that the Islamic message conveyed includes the values of faith, sharia, and morals which are packaged through everyday stories to be easily understood by all groups. Rizky Riplay plays a creative role with a relaxed storytelling style, utilizing conflict and humor so as not to seem patronizing, and actively responding to audience input. The response of subscribers is generally positive, shown by support, suggestions, criticism, and active discussion. The communication pattern techniques used include one way patterns by taking viral phenomena to be used as da'wah animations, two way patterns by responding to comments, and multi directional patterns through discussions between subscribers in the comments column. These results prove that Rizky Riplay's account utilizes new media by using animations on YouTube that are packaged in a relaxed and creative manner that is able to attract young audiences and facilitate the delivery of relevant islamic messages. Abstrak. Penelitian ini bertujuan untuk mengetahui pesan keislaman yang disampaikan dalam konten animasi YouTube Rizky Riplay, Peran Rizky Riplay sebagai komunikator dalam menyampaikan dakwah melalui media animasi di YouTube. Respon subscriber konten akun animasi YouTube Rizky Riplay, dan pola komunikasi dakwah dalam konten animasi YouTube Akun Rizky Riplay. Penelitian ini menggunakan kualitatif deskriptif. Data dikumpulkan melalui wawancara, observasi, dan analisis konten (content analysis). Dengan menggunakan teori New Media Lievrouw & Livingstone. Hasil penelitian menunjukan bahwa pesan keislaman yang disampaikan mencakup nilai akidah, syariah, dan akhlak yang dikemas melalui cerita sehari-hari agar mudah dipahami semua kalangan. Rizky Riplay berperan kreatif dengan gaya bercerita santai, memanfaatkan konflik dan humor agar tidak terkesan menggurui, serta aktif merespons masukan penonton. Respon subscriber umumnya positif, ditunjukkan dengan dukungan, saran, kritik, dan diskusi aktif. Teknik pola komunikasi yang digunakan meliputi pola satu arah dengan mengambil fenomena viral untuk dijadikan animasi dakwah, pola dua arah dengan menanggapi komentar, serta pola multi arah melalui diskusi antar subscriber di kolom komentar. Hasil ini membuktikan bahwa akun Rizky Riplay memanfaatkan media baru dengan menggunakan animasi dalam YouTube yang dikemas secara santai dan kreatif mampu menarik minat audiens muda yang telah mempermudah penyampaian pesan keislaman yang relevan.